Isolasi Dan Identifikasi Jamur Simbion Pada Karang Lunak Sinularia polydactyla Di Perairan Pulau Tegal Dengan Menggunakan Media Yang Berbeda - Reftika Ramona Putri; Rozirwan Rozirwan; Fitri Agustriani (Jurnal Penelitian Sains, 2019)
Soft coral is a marine animal that does not have a spine that lives in shallow water. Soft corals are able to interact with microorganisms such as fungi. Symbiotic fungi from the sea are microbes that are rich in bioactive natural products and secondary metabolites. The purpose of this study was to isolate and identify symbiotic fungi with isolated soft corals from the Sinularia polydactyla type and determine the type of media that produced the most symbiotic fungi in the Sinularia polydactyla soft coral. The research method in isolating fungal symbionts was carried out using the Direct Planting method. This study uses 3 media including PDA (Potato Dexktrose Agart), HDA (Host Dekxtrose Agart), and MEA (Malt Extract Agart). The results of this study showed that symbiotic fungi with Sinularia polydactyla soft coral were isolated in 7 isolates, with 3 isolates identified as Aspergillus flavus, 2 isolates identified as Penicillium sp., and 2 isolates identified as Aspergillus niger. The media that produced the most symbiotic mushrooms were PDA media, where 7 isolates were found, there were 3 isolates that grew on PDA media, 2 isolates on MEA media, and 2 other isolates on HDA media.